2017
DOI: 10.3892/mmr.2017.7521
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of multiple genes in VSMC proliferation induced by Hcy

Abstract: Vascular smooth muscle cell (VSMC) proliferation is a primary pathological event in atherosclerosis (AS), and homocysteine (Hcy) is an independent risk factor for AS. However, the underlying mechanisms are still lagging. Studies have used the combination of methylation of promoters of multiple genes to diagnose tumors, thus the aim of the current study was to investigate the role of methylation status of several genes in VSMCs treated with Hcy. CpG islands were identified in the promoters of platelet‑derived g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Rhee et al (36) revealed that a marked reduction in the number of methylated CpG dinucleotides in the EC-SOD gene were detected in AS aortas compared with normal aortic intima-media. A number of previous studies have reported that Hcy is regulated by the expression of DNMTs, particularly DNMT1 (13,37). In the process of methyl transfer reactions, methionine is converted to Hcy with SAM and SAH as byproducts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhee et al (36) revealed that a marked reduction in the number of methylated CpG dinucleotides in the EC-SOD gene were detected in AS aortas compared with normal aortic intima-media. A number of previous studies have reported that Hcy is regulated by the expression of DNMTs, particularly DNMT1 (13,37). In the process of methyl transfer reactions, methionine is converted to Hcy with SAM and SAH as byproducts.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge there is no direct evidence explaining the mechanisms by which Hcy affects the expression of EC-SOD and disturbs the balance between oxidative-induced AS. Epidemiological studies have demonstrated that a mildly elevated plasma Hcy level is an independent risk factor for the development of AS (13). Hcy is a non-protein, sulfur-containing amino acid, which is formed exclusively by the demethylation of methionine (14).…”
Section: Mechanism Of Extracellular-superoxide Dismutase Dna Methylatmentioning
confidence: 99%
“…The thermal cycler (Funglyn Biotech, Inc., Toronto, ON, Canada) conditions comprised an initial activation step at 95˚C for 5 min, followed by a 2-step PCR program of 95˚C for 15 sec, annealing temperatures for 15 sec and at 72˚C for 30 sec for 30 cycles. Subsequently, the relative alterations in the mRNA expression levels of DNMT1 and PTEN were determined by fold-change analysis, in which the degree of change was calculated as 2 -∆∆Cq , where Cq=(Cq gene -Cq GAPDH ) treatment-(Cq gene -Cq GAPDH ) control (17).…”
Section: Cell Viability Assessment Mtt (Sigma-aldrich; Merckmentioning
confidence: 99%
“…The transfection efficiency was determined by detecting the fluorescence intensity via an inverted fluorescence phase contrast microscope (Olympus IX71, Olympus Corporation, Tokyo, Japan). The transfected VSMCs were treated with Hcy for 24 h and mRNA expression of PTEN/DNMT1 was detected with RT-qPCR (17). Western blotting was carried out to examine the protein expression of PTEN/DNMT1 (17).…”
Section: Ce L L T Ra N S F E C T I O N T H E R E C O M B I N a Nt Pmentioning
confidence: 99%
See 1 more Smart Citation